Modeling for body growth of crossbred piglets - Paul, Amrit Kumar; Singh, Surendra; Singh, K N; Kumar, Ashok; Singh, N Okendro (The Indian Journal of Animal Sciences, 2012)
This paper attempts to describe growth pattern in terms of body weight of crossbred variety (Landrace× desi) of pig for both male and female separately maintained at piggery farm, Indian Veterinary Research Institute (IVRI), Izatnagar. The suitability of the model was established on the criteria of mean absolute error (MAE), root mean squared error (RMSE) and mean absolute predicted error (MAPE). On these criteria, Gompertz model was found to be the best fitted model as the shape of the curve for body weight and predicted weights were also quite closed.